1999
DOI: 10.1507/endocrj.46.59
|View full text |Cite
|
Sign up to set email alerts
|

A Patient With Preclinical Cushing's Syndrome and Excessive DHEA-S Secretion Having Unilateral Adrenal Carcinoma and Contralateral Adenoma.

Abstract: Abstract. We report a case of preclinical Cushing's syndrome in a 54-year-old male associated with bilateral adrenocortical tumours. Physical findings and general laboratory data were unremarkable except for mild hypertension (158/90 mmHg) and impaired glucose tolerance. Endocrinological evaluation revealed the presence of autonomous cortisol secretion including unsuppressible serum cortisol by 8 mg dexamethasone test (11,ug/dl), high serum DHEA-S (3580 ng/ml, normal: 400-3500) and increased urinary 17-KS excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Autonomous cortisol production without clinically overt Cushing's syndrome, termed as subclinical Cushing's syndrome, accounts for 5-12% of adrenal incidentaloma [14,[22][23][24]. However, ACC associated with subclinical Cushing's syndrome has rarely been reported thus far [25,26]. The diagnosis of subclinical Cushing's syndrome in the present case was made by the lack of Cushingoid feature and the following endocrine data; 1) suppression of plasma ACTH; 2) lack of circadian rhythm of cortisol; 3) no response of plasma ACTH and cortisol to CRH stimulation; 4) nonsuppressibility of cortisol to low-and high-dose (1, 2, 8 mg) dexamethasone, and 5) postoperative adrenal insufficiency necessiating cortisol replacement [25].…”
Section: Discussionmentioning
confidence: 99%
“…Autonomous cortisol production without clinically overt Cushing's syndrome, termed as subclinical Cushing's syndrome, accounts for 5-12% of adrenal incidentaloma [14,[22][23][24]. However, ACC associated with subclinical Cushing's syndrome has rarely been reported thus far [25,26]. The diagnosis of subclinical Cushing's syndrome in the present case was made by the lack of Cushingoid feature and the following endocrine data; 1) suppression of plasma ACTH; 2) lack of circadian rhythm of cortisol; 3) no response of plasma ACTH and cortisol to CRH stimulation; 4) nonsuppressibility of cortisol to low-and high-dose (1, 2, 8 mg) dexamethasone, and 5) postoperative adrenal insufficiency necessiating cortisol replacement [25].…”
Section: Discussionmentioning
confidence: 99%
“…It can be named as subclinical (or pre-clinical) Cushing's syndrome, subclinical autonomous glucocorticoid hypersecretion or subclinical hypercortisolism. Beside the Italian Society of Endocrinology study that has revealed four cases of subclinical Cushing's syndrome out of 47 ACC cases (8.5%), in the literature mostly only individual case presentations can be found [33][34][35][36].…”
Section: Hormonal Work-upmentioning
confidence: 99%
“…Androgen-secreting adrenal tumours, mostly carcinomas, are usually associated with the development of Cushingoid features and can be diagnosed as a typically large (> 6 cm) on ultrasound or adrenal computerized tomography. Increased production of adrenal androgens including DHEAS has been shown in patients with carcinoma than that in adenoma [51].…”
Section: Differential Diagnosis and Laboratory Evaluation In Nonpolycmentioning
confidence: 99%